Theoretical framework and protocol for the evaluation of Strong Through Every Mile (STEM), a structured running program for survivors of intimate partner violence - Dayna M. Maniccia; Janel M. Leone (BMC, 2019)
Abstract Background Intimate partner violence can have a devastating impact on victims' psychological and physical health and ability to maintain and preserve interpersonal relationships. The aim of the current study is to empirically test the effectiveness of Strong Through Every Mile (STEM), a 10-week structured running (exercise) program designed to increase psychological, social, and physical well-being among survivors of intimate partner violence. To the authors' knowledge, STEM is the only community-based structured running program designed to improve the quality of life of survivors of intimate partner violence. This paper will describe the STEM program and present the theoretical basis of the program and the program evaluation design. Methods The current study will utilize an interdisciplinary lens to evaluate a community-based intervention aimed at decreasing the negative effects of intimate partner violence on women's lives. The study will use a mixed method approach (qualitative and quantitative), including a pre- and post-test evaluation of the STEM running program. Primary data will be collected using paper and pencil surveys which assess women's psychological, social, and physical well-being prior to participation in the program and following the completion of the program. Qualitative data from focus groups will also be collected and allow for a more rich understanding of the changes that women experience over the course of the program and specific mechanisms underlying these changes. Discussion The current study will employ an interdisciplinary lens to examine the extent to which a structured exercise program, specifically running, impacts the psychological, social and physical well-being of women survivors of intimate partner violence. Findings of this study can influence the development and implementation of similar programs for survivors of intimate partner violence and other types of trauma by identifying mechanisms central in achieving positive outcomes for participants.